Prolactin-secreting pituitary adenomas: male-specific differences in pathogenesis, clinical presentation and treatment - Dzialach, Lukasz; Sobolewska, Joanna; Zak, Zuzanna; Respondek, Wioleta; Witek, Przemysław (Frontiers in Endocrinology, 2024)
Prolactinomas (PRLomas) constitute approximately half of all pituitary adenomas and approximately one-fifth of them are diagnosed in males. The clinical presentation of PRLomas results from direct prolactin (PRL) action, duration and severity of hyperprolactinemia, and tumor mass effect. Male PRLomas, compared to females, tend to be larger and more invasive, are associated with higher PRL concentration at diagnosis, present higher proliferative potential, are more frequently resistant to standard pharmacotherapy, and thus may require multimodal approach, including surgical resection, radiotherapy, and alternative medical agents. Therefore, the management of PRLomas in men is challenging in many cases. Additionally, hyperprolactinemia is associated with a significant negative impact on men's health, including sexual function and fertility potential, bone health, cardiovascular and metabolic complications, leading to decreased quality of life.In this review, we highlight the differences in pathogenesis, clinical presentation and treatment of PRLomas concerning the male sex.